Anadolu Lisesi Öğretmenlerinin Tükenmişlik Düzeylerinin Çeşitli Değişkenlerle İlişkisi - Kıral, Bilgen (Muş Alparslan Üniversitesi, 2018)
The purpose of this research was to investigate the relationship between occupational burnout levels of teachers and various variables. The study was carried out with 294 volunteer Anatolian High School teachers in 2016-2017 academic year in Aydın. The research was designed in a relational screening model which is one of the quantitative research methods. In the study, Maslach Burnout Inventory adapted to Turkish by Ergin (1992) was used. The research data were collected by going to schools.  The collected data were analyzed by SPSS package program. As a result of the research it was determined that the teachers experienced the emotional exhaustion the most. There was no significant difference in burnout levels according to teachers'gender, marital status, and service year in school. In the study age, branch, seniority, education status and occupation were determined as variables affecting burnout. It suggested that teachers can be helped to relax psychologically by carrying out supportive activities such as burnout strategies.

Araştırma Anadolu Lisesi öğretmenlerinin mesleki tükenmişlik düzeylerinin çeşitli değişkenlerle ilişkisini ortaya çıkarmak amacıyla yapılmıştır. Çalışma 2016-2017 akademik yılında Aydın ilinde 294 gönüllü Anadolu Lisesi öğretmeni ile yürütülmüştür. Araştırma nicel araştırma yöntemlerinden ilişkisel tarama modelinde desenlenmiştir. Araştırmada Ergin (1992) tarafından Türkçe’ye uyarlanan Maslach Tükenmişlik Envanteri kullanılmıştır. Araştırma verileri okullara gidilerek toplanmıştır. Toplanan veriler SPSS paket programı ile analiz edilmiştir. Araştırma sonucunda öğretmenlerin en çok duygusal tükenme yaşadığı tespit edilmiştir. Öğretmenlerin cinsiyetine, medeni durumuna ve çalışılan okuldaki hizmet yılına göre tükenmişlik düzeylerinde anlamlı bir farklılık bulunmamıştır. Araştırmada yaş, branş, kıdem, öğrenim durumu ve mesleğini severek yapma durumu tükenmişliği etkileyen değişkenler olarak tespit edilmiştir. Öğretmenlere tükenmişlikle başetme stratejileri hakkında destek faaliyetleri yürütülerek öğretmenlerin psikolojik anlamda rahatlamalarına yardımcı olma gibi önerilerde bulunulmuştur.
Anatolian High School Teachers’ Burnout Levels Related to Various Variables
anemon
Keywords: Teacher; Burnout; Anatolian High School; Öğretmen; Tükenmişlik; Anadolu Lisesi